Manajemen Laba Pada Perusahaan Perbankan: Perubahan Struktur Direksi, Bonus Dewan Direksi, Kebijakan Dividen, dan Perubahan Utang Perusahaan - Made Dwi Cahaya Permana; Dadi Heryana; Amrie Firmansyah (STIE Jambatan Bulan, 2024)
This research aims to determine the effect of changes in the board of directors' structure, board of directors' bonuses, dividend policy, and increase in company debt on earnings management. This research uses a purposive sampling method. The data type used is panel data for 2020-2022 in the form of banking sector company data obtained from the Indonesia Stock Exchange with a total of 137 data. The research uses quantitative research methods with multiple linear regression models. This research indicates that changes in directors and directors' bonuses have no effect on earnings management, while dividend policy has a negative effect on earnings management, and changes in debt have a positive effect on earnings management